Refreshing Extension of the Service Life of Cast High - Chernousenko, Olga Yuriivna; Rindyuk, Dmitro Viktorovich; Peshko, Vitaliy Anatoliyovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2018)
The power-generating units at Kurakhovska Heat Power Plant have already worked off their fleet life. Since cast high-temperature casings are one of the most expensive elements of the steam turbine an issue of the possibility of refreshing extension of their service life remains to be a problem of strategic importance. This scientific paper gives the computation data of thermal and elastically deformed states of the casings of high-pressure cylinders (HPC) and average-pressure cylinders (APC) for the turbine K-200-130-3 during the main operation modes. To do the computations we used the state-of-the-art methods of mathematical simulation. The availability of service-induced damages in the design structure and the results of repair and restoration changes were taken into account. An estimation of the low-cycle fatigue and durable strength done in compliance with current normative documents is indicative of the exhaust of life indices of the basic metal of casing elements. However, previous investigations of the physical and mechanical structure of metal with the exhausted fleet life allow us to use lower coefficients of the margin of safety. The service life of the casings of HPC and APC of the power-generating unit No4 at Kurakhovska Heat Power Plant can be extended by 50 thousand hours and that of the power-generating unit No 5 by 45 thousand hours after the expert commission adopts the coefficients of the margin of safety at the level of 3 for the number of cycles and at the level of 1.25 for the strain.